2011
DOI: 10.1186/1550-2783-8-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the nutrition knowledge of sports department students of universities

Abstract: BackgroundIndividuals who have knowledge on the importance of adequate and balanced diet and reflect this knowledge to their behaviors are considered to be more successful in sports life. The present study aims to evaluate the nutrition knowledge of students receiving sports education in universities.MethodsThe study sample consists of 343 voluntary students from the Sports Departments of Hacettepe, Gazi and Ankara Universities in Ankara. The questionnaire used in the study included a demographic section, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
6
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 17 publications
6
70
6
3
Order By: Relevance
“…This concern has been observed in a study in Osun state that assessed food aversion during pregnancy (Ogunjuyigbe, . This implies that nutrition knowledge alone may not necessarily be sufficient to initiate behavioral application of healthy diets (Ozdoğan and Ozferzcelik, 2011). A surprising finding in this study is the avoidance of foods because of the perceived adverse health effect of some healthy foods.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This concern has been observed in a study in Osun state that assessed food aversion during pregnancy (Ogunjuyigbe, . This implies that nutrition knowledge alone may not necessarily be sufficient to initiate behavioral application of healthy diets (Ozdoğan and Ozferzcelik, 2011). A surprising finding in this study is the avoidance of foods because of the perceived adverse health effect of some healthy foods.…”
Section: Discussionmentioning
confidence: 69%
“…This study also revealed that earning more income is a determinant of food restriction due to cultural taboos. This finding can be explained by the fact that a higher income subsequently result in access to a variety of food (Ozdoğan and Ozferzcelik, 2011). Pregnant women of low socioeconomic status in developing countries are noted for insufficient protein and energy food intake (Wright, Hoffman, and Savitz, 2010;Beydoun and Wang, 2008;ADA, 2005).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A continuing problem associated with gaining an understanding of knowledge and knowledge structures is the need for reliable and valid measures of nutrition knowledge (22) . Numerous studies have aimed to assess nutrition knowledge in Turkey (23)(24)(25)(26)(27)(28) . These studies usually employed specific questionnaires intended to measure the nutrition knowledge of sub-populations (such as adolescents, physicians, interns, university students, students studying sports education).…”
mentioning
confidence: 99%
“…Nutrition is an important complement of any physical fitness program. The main dietary goal for active supplement information from nutritionists/dietitians and individuals is to obtain adequate nutrition to optimize health and fitness or sports performance (Ozdoğan & Ozcelik, 2011). It is well recognized that optimal nutrition can enhance athletic performance.…”
Section: Introductionmentioning
confidence: 99%